Analysis of the Role of Facial Expression in Media Presence in the Development of Social, Emotional, and Expressive Language Skills in Children Aged 3-4 Years - Lailil Murro Nuril Chasanah; Rachma Hasibuan (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to analyze the role of facial expression media in developing social-emotional and expressive language skills in children aged 3-4 years. A qualitative descriptive method was used, with data collected through observations and interviews at several kindergartens. The results indicate that media such as hand puppets, picture books, and digital applications displaying facial expressions significantly contribute to the enhancement of emotion recognition and expression, as well as the development of children's expressive language. This research recommends the integration of facial expression media into early childhood education curricula to support their holistic development.